PERANCANGAN SISTEM INFORMASI DATA E-LEARNING BERBASIS WEB PADA SMP/SMA SOLIDEO BSD - Dalton F Munthe Rasnika Sihite; Surtikanti (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
The e-learning system is absolutely necessary to anticipate the times with the support of information technology where everything is heading to the digital era, both mechanism and content. In its development, the system must be preceded by analyzing the needs of the user (user needs). E-learning is an electronic learning system, where students or students do not need to sit in class to listen to any learning material delivered by the teacher directly, but can be listened to at any time in any place that is connected to internet facilities. Solideo BSD School has problems to continue to be connected to each other even though they are not face to face so that the teaching and learning process continues without any obstacles. Some of the problems that form the basis of this research include the absence of online during/online-based learning media that can be accessed anytime and anywhere, thus hampering the learning process. The teaching and learning activities of teachers are limited because they are only carried out in class face-to-face. One of the efforts to improve the quality of education is by utilizing information technology, namely by using web technology to support the process of teaching and learning activities in the classroom, or commonly known as E-Learning.